HSRC Investigation into Intergroup Relations - H.C. Marais; L. Dreyer (Communicare)
This article provides information on the background to and the manage- ment of the HSRC Investigation into Intergroup Relations. At the ame time it is also an invitation to the research community to participate in the programme by applying for financial assistance. Communication scientists in particular and social scientists in general are invited to participate in the HSRC Investigation into Intergroup Rela- tions. A budget independent of the usual financing of research at universities is available for research into the most pressing aspects of the relationships between the major groups in South Africa.